Abdominal X-ray might be a useful tool for assessing medication adherence in patients receiving Lanthanum carbonate - Hiroaki Ogata; Fumihiko Koiwa; Eriko Kinugasa; Tadao Akizawa (The Korean Society of Nephrology, 2012)
Control of the serum phosphate (P) level is the most important and challenging in dialysis patients, because hyperphosphatemia is closely associated with higher cardiovascular morbidity and mortality. Lanthanum carbonate (LC), which is a novel non-calcium phosphate P binder, is effective in decreasing the serum P level and is well-tolerated with fewer adverse effects. However, LC has been reported that ingested LC fragments could be detectable in abdominal X-ray and computed tomography, because its density is between that of bone and metal. We performed an observational study to assess the relationship clinical effects of LC and abdominal X-ray findings in dialysis patients receiving LC. The enrolled 39 patients (female 7 (17.9%), age 59.6 yrs, dialysis vintage 11.2 yrs, diabetes 15 (38.5%)) were made abdominal X-ray examination at 4, 8, and 12 weeks after LC administration. Serum albumin, creatinine, and alkaline phosphatase levels did not change significantly during the 12-week treatment period. The P and the parathyroid hormone levels decreased after LC administration. Abdominal X-ray examination revealed digested LC tablets, in a variety of forms, through the intestinal tract in 37 patients (94.9%). The two patients without any digested LC fragment were still hyperphosphatemic after LC prescription, and they admitted not to have taken LC. Their serum P levels rapidly decreased after a series of medication counseling. In conclusion, this study suggested that abdominal X-ray might be useful tool for assessing medication adherence in patients receiving LC.